2016
DOI: 10.1136/bjophthalmol-2015-308074
|View full text |Cite
|
Sign up to set email alerts
|

Short-term choroidal thickness changes in patients treated with either ranibizumab or aflibercept: a comparative study

Abstract: A greater decrease in choroidal thickness was noted in eyes treated with aflibercept than in eyes treated with ranibizumab. This difference was more marked in PCV than in other subtypes of neovascular AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Recently Kim et al [14] and Yun et al [15] reported that intravitreal injection of aflibercept significantly decreased subfoveal choroidal thickness more than ranibizumab.…”
Section: Discussionmentioning
confidence: 97%
“…Recently Kim et al [14] and Yun et al [15] reported that intravitreal injection of aflibercept significantly decreased subfoveal choroidal thickness more than ranibizumab.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, type 1 PCV with thinner subfoveal CT appears to be associated with AMD in which reduced choroidal blood volume was exhibited 13 26. The suppression of CVH and vasoconstriction induced by aflibercept27 28 may be more prominent in type 2 PCV with greater vessel diameter, and may lead to greater reduction of subfoveal CT. A comparative study of subfoveal CT changes between PCV and typical NV-AMD after anti-VEGF treatment reported that patients with PCV showed thicker baseline subfoveal CT and greater reduction of subfoveal CT to aflibercept than patients with typical NV-AMD 29…”
Section: Discussionmentioning
confidence: 99%
“…similarly used mean choroidal thicknesses measured by OCT as a treatment outcome after initiation of either intravitreal ranibizumab and aflibercept in three disease groups of NV-AMD, PCV and retinal angiomatous proliferation (RAP) and showed significant differences in amount of decrease in the two treatment groups as well as difference between disease groups. (64) Though OCT measurements of choroidal thickness provide valuable clinical information, some caution using it as a sole measure of treatment response, since it can be influenced by diurnal variations and systemic conditions. (65,66)…”
Section: Imaging Of Pcvmentioning
confidence: 99%